Women theatre directors in Malaysia: a comparative study of Rohani Md. Yousoff and Fauziah Nawi / Syarafina Abdullah - Abdullah, Syarafina (2016)
This study is an overview of the two most experienced and established Malay women directors in Malaysia's modern Malay theatre scene. Rohani Md. Yousoff and Fauziah Nawi are two early prolific directors who had successfully staged professional productions during the latter part of the twentieth century. These two women directors undoubtedly are deserving of more attention for the significant impact they had made as directors in the Malay Theatre. Unfortunately, their contributions had not received as much acknowledgement or recognition as they truly deserve. To address this sho11coming, biographical details including information on their training and career paths, productions, awards, bibliographic materials, critical receptions covering their directing styles have been collected as an endeavor to fill in that artistic gap to address the missing information on women's involvement as directors in the Malay theatre world. Applying Aristotle's dramatic theatre and Brecht's epic theatre theories on the six theatre performances being focused on in this study; both directors with three theatre performances each managed to align these theoretical approaches towards directing their stage plays. The research findings will also help to recognize the many overlooked contributions of these women directors and henceforth empower other women directors interested in delving into the Malay theatre arena.